2010
DOI: 10.1073/pnas.0914242107
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear phosphoinositide 3-kinase β controls double-strand break DNA repair

Abstract: Class I phosphoinositide 3-kinases are enzymes that generate 3-poly-phosphoinositides at the cell membrane following transmembrane receptor stimulation. Expression of the phosphoinositide 3-kinase β (PI3Kβ) isoform, but not its activity, is essential for early embryonic development. Nonetheless, the specific function of PI3Kβ in the cell remains elusive. Double-strand breaks (DSB) are among the most deleterious lesions for genomic integrity; their repair is required for development. We show that PI3Kβ is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
140
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 39 publications
5
140
0
Order By: Relevance
“…27 However, LY294002 also inhibits DNA-PKcs at concentrations similar to those that inhibit PI3K and LY294002-induced radiosensitivity correlates with inhibition of DNA-PKcs, 53 making interpretation of these data difficult. In contrast, our data suggest that DSB-induced pAKT-S473 accumulation is PI3K-independent, which may have important ramifications for the potential utility of novel radiosensitizing agents that target AKT via the ablation of PI3K-dependent signaling, since our model predicts that these agents may not affect the DSB-induced, PI3K-independent phosphorylation of pAKT-S473.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…27 However, LY294002 also inhibits DNA-PKcs at concentrations similar to those that inhibit PI3K and LY294002-induced radiosensitivity correlates with inhibition of DNA-PKcs, 53 making interpretation of these data difficult. In contrast, our data suggest that DSB-induced pAKT-S473 accumulation is PI3K-independent, which may have important ramifications for the potential utility of novel radiosensitizing agents that target AKT via the ablation of PI3K-dependent signaling, since our model predicts that these agents may not affect the DSB-induced, PI3K-independent phosphorylation of pAKT-S473.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The canonical mechanism of AKT phosphorylation involves PI3K, which is present in the nucleus and accumulates at DSB, 27 although PI3K-independent mechanisms have been described. [28][29][30] To assess whether PI3K is required for the MRE11-dependent accumulation of pAKT-S473, we utilized the PI3K inhibitor LY294002, which blocks both endogenous and seruminduced pAKT-S473 in normal fibroblasts (Sup.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Activation of the PI3K pathway is a common feature of many tumor types and leads to the stimulation of cell growth, mobility, survival, and metabolism ( 7 ), and also sensing of DSBs during DNA repair ( 8 ).…”
mentioning
confidence: 99%
“…161 However, in addition to the role of p110a in the DNA damage response, activation of p110b by DNA damage seems to play a critical role in recognition of DNA double-strand breaks and recruitment of NBS1 to sites of DNA damage. 162 Loss of p110b leads to impaired recruitment of downstream DNA damage repair mediators such as ATM, RAD17, g-H2AX, and 53BP. 162 In contrast to AKT, several reports have shown that mTORC1 signaling is actually downregulated as a result of DNA damage.…”
Section: Combination Of Pi3k and Mek Inhibitorsmentioning
confidence: 99%
“…162 Loss of p110b leads to impaired recruitment of downstream DNA damage repair mediators such as ATM, RAD17, g-H2AX, and 53BP. 162 In contrast to AKT, several reports have shown that mTORC1 signaling is actually downregulated as a result of DNA damage. [163][164][165] Oxidative stress was shown to downregulate mTORC1 signaling by activating ATM, leading to a phosphorylation chain resulting in sequential activation of LKB1, AMPK, and finally TSC2.…”
Section: Combination Of Pi3k and Mek Inhibitorsmentioning
confidence: 99%